Konstruksi Makna Tayangan Indonesia Bersatu Debat Capres-Cawapres PILPRES 2009 DI Metro TV - Damayanti, Novita (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2013)
This research focus the constructive meaning from Metro Tv on presidential and vice-presidentcandidacy debate in Presedential election 2009. Qualitative research method with a constructiveparadigm is used in this research. A case study approach is seen to best describe the political publicrelations activities in this research. This research is divided into two parts, first, a visual framinganalysis on Metro TVThe findings showed that the meaning construction on Metro TV in a debate broadcast In Indonesiabersatu through a frame: The debate 2009 which is a democratic party of a political event of theIndonesians. The constructive meaning broadcasted on Metro Tv tries to give an understanding to theIndonesians especially the viewers to become a rational voters, not an emotional ones by broadcastinga discussion on the presidential debate 2009.